(3MhGTi Ydi GdahGFO GdVjGFjIs - (3EHQGgje Hf eMeO Hf YQH TGg GdCSaQGjfi YUGe GdOjfs; (3fhQ GdOjf YHO GdQMef Hf CMeO Hf eMeO GdLGej GdfbTHfOj, GdLGej,J (B898 (3g` s
(3ChdgG (B:s
(3jG gGOjkG dSGdc eSGdc eMGeOc hHYO ajbhd GdYHO GdabjQ gPg MhGTi cdGTeS ddfLhe bhdg GdMeO gh GdhUa HGdLejd Ydi GdLejd s
(3BNQgG (B:s
(3bhdg hGdeaJhM eG bHdgG JbdH CdaG Ydi Cf GdGHJOGA ceG JaQO ai eMdg ahLH Cf dGJcJH GdNajaI Je s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1372s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9274) s
Keywords: (3GdfMhs